Petrographic and geochemical characterization of the Upper Cretaceous coal and mudstones of Gombe Formation, Gongola sub-basin, northern Benue trough Nigeria: Implication for organic matter preservation, paleodepositional environment and tectonic settings - Ayinla, H.A. (Elsevier B.V., 2017)
Under-exploration of the Upper Cretaceous petroleum systems in the Northern Benue Trough Nigeria has been attributed largely to lack of subsurface samples and non-integration of organic and inorganic geochemical methods. Recent access to surface sampling from Maiganga coalfield revealed a need for detailed evaluation of the sedimentary facies types for better understanding of the hydrocarbon potential of the area. Detailed maceral point count, Py-GC, CHNSO as well as major oxides and trace element (ICP-MS) analysis were used to characterize the Gombe Formation coals and the mudstones for determination of the organic matter origin, preservation, paleodepositional environment, tectonic setting and paleoclimatic condition during sedimentation. Evaluation based on the maceral composition, TPI, GI values, plot of trace elements V versus Ni and sedimentary succession suggest deposition of predominantly terrigenous organic matter (45 to 73 huminite maceral) in an upper deltaic setting for the Maiganga facies. The maceral analysis associated with Py-GC studies indicates that the sedimentary facies of Gombe Formation have potential to generate liquid hydrocarbon. This can be estimated from an average of 21.50 liptinite content and the ternary plot of the Py-GC pyrolysate m(+ p) xylene, n-octene and phenol suggesting presence of Type II and Type II/III kerogen within the basin. Assessment of the paleodepositional environment based on the trace elements composition indicates a moderate stratified water column and salinity within a relatively sub-oxic to oxic conditions during sedimentation. The major oxide composition as well as the binary plots of SiO2 versus (Al2O3 + K2O + Na2O) and log SiO2 versus (K2O/Na2O) for the shales and mudstones revealed a predominance of semi-arid to slightly humid-warm paleoclimatic conditions and a passive continental margin setting. This is in accordance with the Cretaceous tectonic events of the West and Central Africa which affected the petroleum system in the entire Benue Trough. © 2017 Elsevier B.V.